THE RELATIONSHIP BETWEEN TERMINOLOGY AND THE TERMINOSYSTEM - Yuan Xiaowei (Scholar Express Journal, 2021)
This article discusses the theoretical foundations of the study of sports terminology. In addition, information is provided on the relationship between terminology and the terminosystem
Keywords: terminology; terminosystem; research; sports terms